Advantages of Database Management System in Cloud Infrastructure - pandey, Rajneesh kumar; singh, Yashwant kumar; Milan, Ram (IJRDO -Journal of Computer Science Engineering, 2017)
The challenge of building consistent, available, and scalable data management systems capable of serving peta bytes of data for millions of users has confronted the data management research community as well as large internet enterprises. A Cloud database management system is a distributed database that delivers computing as a service instead of a product. It is the sharing of resources, software, and information between multiple devices over a network which is mostly the internet. It is expected that this number will grow significantly in the future. As a result, there is a growing interest in outsourcing database management tasks to third parties that can provide these tasks for much lower cost due to the economy of scale just like putting it into the cloud. The cloud is used as a storage location and database can be accessed and computed from anywhere. The large number of web application makes the use of distributed storage solution in order to scale up. It enables user to outsource the resource and services to the third party server. In this paper, we discuss the recent trend in cloud service based on database management system and offering it as one of the services in cloud. We also proposed an architecture of cloud based on database management system.